Generation and Characterization of α9 and α10 Nicotinic Acetylcholine Receptor Subunit Knockout Mice on a C57BL/6J Background - Morley, Barbara J.; Dolan, David F.; Ohlemiller, Kevin K.; Simmons, Dwayne D. (Frontiers in Neuroscience, 2017)
We generated constitutive knockout mouse models for the α9 and α10 nicotinic acetylcholine receptor (nAChR) subunits by derivation from conditional knockouts by breeding with CRE deleter mice. We then backcrossed them onto a C57BL/6J genetic background. In this manuscript, we report the generation of the strains and an auditory phenotypic characterization of the constitutive α9 and α10 knockouts and a double α9α10 constitutive knockout. Although the α9 and α10 nAChR subunits are relevant to a number of physiological measures, we chose to characterize the mouse with auditory studies to compare them to existing but different α9 and α10 nAChR knockouts (KOs). Auditory brainstem response (ABR) measurements and distortion product otoacoustic emissions (DPOAEs) showed that all constitutive mouse strains had normal hearing. DPOAEs with contralateral noise (efferent adaptation measurements), however, showed that efferent strength was significantly reduced after deletion of both the α9 and α10 subunits, in comparison to wildtype controls. Animals tested were 3-8 wks of age and efferent strength was not correlated with age. Confocal studies of single and double constitutive KOs showed that all KOs had abnormal efferent innervation of cochlear hair cells. The morphological results are similar to those obtained in other strains using constitutive deletion of exon 4 of α9 or α10 nAChR. The results of our physiological studies, however, differ from previous auditory studies using a α9 KO generated by deletion of the exon 4 region and backcrossed onto a mixed CBA/CaJ X 129Sv background.